2014
DOI: 10.1007/s12028-013-9945-8
|View full text |Cite
|
Sign up to set email alerts
|

ADMA Levels and Arginine/ADMA Ratios Reflect Severity of Disease and Extent of Inflammation After Subarachnoid Hemorrhage

Abstract: ADMA increased significantly after SAH, and the increase in ADMA started after the pro-inflammatory markers (CRP and IL-6) had peaked. This might indicate that endothelial dysfunction, with ADMA as a marker, is induced by a systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A study on patients with subarachnoid haemorrhage observed an initial significant decrease in ADMA 49-72 h after the insult, followed by a delayed increase 97-120 h after the insult. 24 A similar study observed a sudden decrease in RHI day zero to two while ADMA was stable until a significant increase at day six to eight. Thus, an increase in ADMA may occur in the later postoperative period not monitored in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…A study on patients with subarachnoid haemorrhage observed an initial significant decrease in ADMA 49-72 h after the insult, followed by a delayed increase 97-120 h after the insult. 24 A similar study observed a sudden decrease in RHI day zero to two while ADMA was stable until a significant increase at day six to eight. Thus, an increase in ADMA may occur in the later postoperative period not monitored in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…Inflammation per se is also associated with an increased risk for atherosclerosis, cardio-, and cerebrovascular diseases (12,28). Previous studies in SAH patients have revealed that the marker for endothelial dysfunction, asymmetric dimethylarginine (ADMA), increases in the acute phase after SAH (31)(32)(33). Other cerebrovascular causes = Other non-traumatic intracranial haemorrhage (I62), acute cerebrovascular insufficiency and chronic cerebral ischaemia (I67), stroke and occlusion not specified as haemorrhage or infarction (I64, I66), cerebrovascular disorders in diseases classified elsewhere (I68).…”
Section: Discussionmentioning
confidence: 99%
“…This pronounced stress response is followed by a considerable systemic inflammatory response (5,29,30). Previous studies in SAH patients have revealed that the marker for endothelial dysfunction, asymmetric dimethylarginine (ADMA), increases in the acute phase after SAH (31)(32)(33). ADMA is an endogenous competitive inhibitor of nitric oxide synthase and is reported as an independent risk factor for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is another life‐threatening condition accompanied by an activated inflammatory response . Hemodynamic instability and possible myocardial dysfunction are complications that can occur and require monitoring and treatment at a neurointensive care unit (NICU) …”
Section: Introductionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is another life-threatening condition accompanied by an activated inflammatory response. 5 Hemodynamic instability and possible myocardial dysfunction are complications that can occur and require monitoring and treatment at a neurointensive care unit (NICU). [6][7][8][9] Meeting the altered physiologic and metabolic needs following a severe brain injury is essential for survival, and the activation of the hypothalamic-pituitary-adrenal (HPA) axis plays an important role.…”
mentioning
confidence: 99%